2021
DOI: 10.1186/s12883-020-02028-0
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of pediatric readmissions among patients with neurological conditions

Ryan O’Connell,
William Feaster,
Vera Wang
et al.

Abstract: Background Unplanned readmission is one of many measures of the quality of care of pediatric patients with neurological conditions. In this multicenter study, we searched for novel risk factors of readmission of patients with neurological conditions. Methods We retrieved hospitalization data of patients less than 18 years with one or more neurological conditions. This resulted in a total of 105,834 encounters from 18 hospitals. We included data on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 15 publications
1
2
0
Order By: Relevance
“…Similar to other studies, this study showed that patients with Medicaid as their primary insurance had a higher likelihood of readmission [ 27 , 28 ]. A study in the adult population has shown that about half of the Medicaid patients did not have an outpatient follow-up between their initial visit and unplanned 30-day readmission [ 29 ].…”
Section: Discussionsupporting
confidence: 89%
“…Similar to other studies, this study showed that patients with Medicaid as their primary insurance had a higher likelihood of readmission [ 27 , 28 ]. A study in the adult population has shown that about half of the Medicaid patients did not have an outpatient follow-up between their initial visit and unplanned 30-day readmission [ 29 ].…”
Section: Discussionsupporting
confidence: 89%
“…The significant risk factors were inconsistently defined across predictive models, allowing a direct comparison only to a limited extent. ORs for comorbidity ranged from 1.01 72 to 10.08 58 across predictive models. A length of stay of ≥15 days (OR=2.39) 61 and a postoperative length of stay of >4 days (hazard ratio=3.12) 56 were considered to be a major risk factor.…”
Section: Resultsmentioning
confidence: 99%
“…bronchial asthma, seizure disorders, nephrotic syndrome and congenital heart diseases, requiring more frequent readmissions than one-time events, e.g . infections 15 , 33 . Similarly, the disorders with high mortality will expectedly have lower readmission rates.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, the disorders with high mortality will expectedly have lower readmission rates. While there is a paucity of Indian literature on this aspect, many studies from the developed countries have also reported the age, diagnosis on index admission and presence of chronic conditions as risk factors for readmissions in children 3 , 7 , 30 , 31 , 33 - 37 . Some others have also found gender, length of hospital stay during the index admission, number of past admissions and presence of comorbidities as significant risk factors for readmissions 3 , 32 , 35 , 36 , 38 , 39 .…”
Section: Discussionmentioning
confidence: 99%